Optimization Of Local Potential In Ketupat Village, Raas District Through Food Product Processing - Nurjanah; Achmad Pradana; Muh. Rudi Nugroho; Putra, Rosyid Nur Anggara (Journal of Islamic Economy and Community Engagement, 2022)
Ketupat Village is a village where most of the population has livelihoods in agriculture and fisheries. The local potentials owned by the Ketupat Village have not been maximally empowered, especially the empowerment of human resources and the potential of local villages such as agricultural products and fisheries. This research is about optimizing local potential through training in making fish and chips products. The aim is to form a small business community (home industry) as a place provided for self-employment, so that people in the future have additional income that can be used for household needs. Keywords: Procesessed product, community empowerment, small business community Abstrak Desa Ketupat merupakan desa yang sebagian besar penduduknya memiliki mata pencaharian di bidang pertanian dan perikanan. Potensi-potensi lokal yang dimiliki oleh Desa Ketupat ini belum dapat diberdayakan secara maksimal terutama pemberdayaan sumber daya manusia dan potensi lokal desa seperti hasil-hasil pertanian, dan perikanan. Penelitian ini berisi tentang cara mengoptimalkan potensi lokal melalui pelatihan pembuatan produk peyek ikan dan keripik. Tujuannya adalah untuk membentuk usaha kecil masyarakat (home industry) sebagai wadah yang disediakan untuk berwiraswasta, sehingga masyarakat ke depan memiliki penghasilan tambahan yang dapat digunakan untuk keperluan rumah tangga.